Revision of the genus Xenophysa Boursin, 1969 (Lepidoptera, Noctuidae) - Varga, Zoltán (Zootaxa, 2011)
The genus Xenophysa Boursin, 1969 is revised. The revision contains the description of a new subgenus Paraxenophysa, and of a new species Xenophysa pseudopoecila, re-description of 2 species and revised status of 4 species. The genus is considered to include 12 species. The distribution and phylogeny of the genus is reviewed. Identification keys based on the male and female genitalia and maps of distribution of all known taxa are given.